بعض مشكلات التكوين الجامعي بالجزائر: الحلول والاقتراحات - جلول, أحمد (University of Eloued جامعة الوادي, 2017)
لقد شهد قطاع التعليم العالي في الجزائر اتساعا واسعا في عدد المؤسسات الجامعية وذلك نتيجة الطلب المتزايد على التكوين الجامعي، فالأعداد الهائلة من الطلبة والمتزايد عددهم عند كل دخول جامعي وضع القائمين على هذا القطاع أمام جملة من التحديات المختلفة من أجل الوصول إلى تكوين ناجع يرقى إلى متطلبات سوق الشغل والتي من بينها رفع قدرات التأطير وزيادة عدد الهياكل البيداغوجية وتحسين برامج التكوين...الخ، فبالرغم من الجهود المبذولة للنهوض بالتكوين الجامعي إلى مصاف الدول الكبرى، إلا أنه ما يزال يعاني الكثير من المشكلات التي تعيق الوصل إلى تكوين جامعي ناجع بكل المقاييس، وهو ما سنحاول التطرق إليه من خلال هذه الورقة من خلال عرض أهم المشكلات التي يعاني منها التكوين الجامعي بالجزائر ومن ثمَّ اقتراح بعض الحلول للتغلب على تلك المشكلات The high education sector in Algeria has witnessed a wide expansion in the number of university institutions due to the increasing demand for university training ,the huge number of students and the increasing number at each university entry put the sector's managers in front of a number of different challenges in order to reach an effective configuration that meets the requirements of the labor market Including raising the capacity of framing, increasing the number of pedagogical structures, improving training programs, etc. Despite efforts to promote university training to the ranks of major countries . However, he is still suffering from many problems that hinder the connection to a successful university formation by all standards, which we will try to address through this paper by presenting the most important problems experienced by university training in Algeria and then propose some solutions to overcome these problems.
Some problems of university formation in Algeria - solutions and suggestions
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: الجامعة، التكوين الجامعي; University, University formation